Study of Teachers' Participation in Mentoring Activities in Schools (Using the Example of St. Petersburg) - S.Y. Trapitsin; O.A. Granichina; E.N. Agapova; M.V. Zharova (Moscow State University of Psychology and Education, 2024)
The article is devoted to the study of the motivation and readiness of teachers to implement the target model of mentoring in order to identify and evaluate the factors influencing this process. We considered theoretical foundations of the organization of mentoring, possible approaches to the study of strategies for the behaviour of teachers during its implementation, and gave the characteristics of their manifestations. The results of study were obtained on a sample of teachers from 4 secondary schools in one of the districts of Saint Petersburg. We used the methods “Motivational profile”, “Determination of the motives of teachers’ work activity”, “Motivational readiness of the teaching staff to master innovations”, “Barriers preventing the development of innovations”, based on generally accepted methodology, proven research design, methods of data collection and analysis, which minimize the impact of systematic and random errors, reduce the reliability of the data. The results obtained show that teachers from different schools have similar characteristics of readiness for mentoring activities, which is largely determined by the level of motivation of teachers, the nature of their attitude towards mentoring, and the degree of understanding of its necessity and importance.